Accurate assembly of ferrocene-functionalized Ti22Fc4 clusters with photocatalytic amine oxidation activity. Issue 22 (18th February 2021) - Han, Er-Meng; Yu, Wei-Dong; Li, Lei-Jiao; Yi, Xiao-Yi; Yan, Jun; Liu, Chao
Abstract : The assembly of the large ferrocene-functionalized Ti22 Fc4 cluster may occur via the coalescence of its two substructures, Ti11 Fc2 and Ti5 Fc, which can also be synthesized independently through subtle changes in reaction conditions. Abstract : We report here the synthesis of a ferrocene-functionalized Ti22 Fc4 cluster with a 'dimer-of-clusters' topology, which represents the largest Ti-oxo cluster (TOC) modified with organometallic groups ever reported. The exact assembly path of Ti22 Fc4 can be inferred from its two substructures, Ti11 Fc2 and Ti5 Fc, which can also be synthesized independently through subtle changes in reaction conditions. Furthermore, we used these clusters as photocatalysts, and have studied, for the first time, the photocatalytic activity of TOCs in the oxidative coupling of amines.